The demography and epidemiology of human health and aging - Siegel, Jacob S. (Springer Netherlands, 2012)
With this book, Siegel, an internationally known demographer and gerontologist, has made a unique contribution to the fledgling fields of health demography, and the demography and epidemiology of aging. The book represents a felicitous union of epidemiology, gerontology, and demography, and appears to be  the first and only comprehensive text on this subject now available. Drawing on a wide range of sciences in addition to demography, gerontology, and epidemiology, including medical sociology, biostatistics, public policy, bioethics, and molecular biology, the author treats theoretical and applied issues, links methods and findings, covers the material internationally, nationally, and locally, and while focusing on the elderly, treats the entire life course. The methods, materials, and pespectives of demography and epidemiology are brought to bear on such topics as the prospects for future increases in human longevity, the relative contribution of life style, environment, genetics, and chance in human longevity, the measurement of the share of  healthy years in total life expectancy, the role of population growth in the rising costs of health care, and the applications of health demography in serving the health needs of local communities. The separate chapters systematically develop the topics of the sources and quality of health data; mortality, life tables, and the measurement of health status; the  interrelationships of health, on the one hand, and mortality, fertility, migration, and age structure, on the other; health conditions in the less developed countries; the concepts and theories of aging and projections of the aged population; and local health applications, public health policy, and bioethical issues in health demography. Given its comprehensiveness, clarity, interdisciplinary scope, and authencity, this book appeals to a wide range of users, from students and teachers of medical sociology, the demography of aging, and public health studies to practitioners in these areas, both as a text in health demography and the demography/epidemiology of aging, and as a reference work in these fields.